Is each of the following binomials a factor of the polynomial P(x) = x3 + 3x2 - x - 3? Explain your answers.

a.x - 1

b.x + 1

c.x - 3

d.x + 3

#### Top Answer

we intially start by rational root theorem So we get x=-1 as its root... View the full answer

#### Sign up to view the full answer

#### Other Answers

Let me explain the... View the full answer

- to figure this out, start plugging x-1=0 so x=1 into the equation which will be one root
- Julia.S
- Jul 20, 2016 at 11:28am

- likewise for the other 2
- Julia.S
- Jul 20, 2016 at 11:29am

Hello, x³ + 3 x² - x - 3 = (x³ - x) + (3x² - 3) = x(x² -... View the full answer

x 3 + 3x 2 - x - 3 = x 3 -x + 3x 2 - 3... View the full answer

a. P(1) = 1 + 3 - 1 - 3 = 0 yes it is a factor b. P(-1) = -1 + 3 +1... View the full answer